Growth during the first year in infants affected by neonatal abstinence syndrome - Tammy E. Corr; Eric W. Schaefer; Ian M. Paul (BMC, 2018)
Abstract Background Infants with neonatal abstinence syndrome (NAS) initially experience neurologic excitability, poor feeding, and/or hyperphagia in the setting of increased metabolic demand. Because the longitudinal effects of these early symptoms and behaviors on weight trends are unknown, we sought to contrast weight gain patterns through age 1 year for infants diagnosed with NAS with matched controls. Methods Retrospective cohort of 70 singletons with a gestational age of ≥37 weeks and an ICD-9 or ICD-10 diagnosis of NAS made ≤7 days after birth with institutional follow-up matched to patients without NAS. Infants were matched on gestational age (±2 weeks), birth weight (±20 g), sex (exact), and insurance type (exact). Quantile regression methods were used to estimate 10th, 25th, 50th, 75th and 90th percentiles of weight over time. Results The mean gestational age for an infant with NAS was 38.8 weeks (standard deviation [SD], 1.3). The mean birth weight was 3.141 kg (SD, 0.510). NAS patients had a median of 24 weights recorded between birth and 400 days (inter-quartile range [IQR], 16-32 weights). Patients without NAS had a median of 12 weights recorded (IQR, 10-16). Growth curves were similar over the first 400 days of life. Patients with NAS had non-significantly higher and lower estimated weights for the 90th and 10th percentiles, respectively. Conclusion Infants with a diagnosis of NAS grew similarly to controls during their first year. Given the frequently-encountered NAS symptoms of hyperphagia and irritability, future studies may evaluate whether early differences in caregiver feeding exist and whether they have longer-term impacts on growth.